ANALISIS RENCANA DAN REALISASI PROGRAM KEGIATAN CORPORATE SOCIAL RESPONSIBILITY PT PLN (PERSERO) - Nadim, Sy; Matsum, Junaidi H.; Ulfah, Maria (Universitas Tanjungpura, 2023)
This research is entitled